Unveiling the hidden risks: albumin-corrected anion gap as a superior marker for cardiovascular mortality in type 2 diabetes: insights from a nationally prospective cohort study - Wang, Mingsi; Yang, Shu; Deng, Jingwen; Wu, Dehai; He, Changzhi; Li, Guanghua; Dong, Ying; Zhang, Yongxiang; Li, Yilan (Frontiers in Endocrinology, 2024)
Aims: Hypoalbuminemia can lead to underestimations of the true anion gap levels.There are few data on albumin-corrected serum anion gap (ACAG) status and mortality in the diabetes. The study aimed to examine the association between ACAG and all-cause, cardiovascular, and cancer mortality in type 2 diabetes (T2D) patients.Methods: Herein, 8,161 diabetic adults were included in the National Health and Nutrition Examination Survey (NHANES) 1999-2018. National Mortality Index (NDI) data were used for determining mortality outcomes through 31 December 2019. Cox proportional hazards models were used to estimate the risk of all-cause, cardiovascular, and cancer mortality. We conducted a mediation analysis using the counterfactual framework method to estimate how ACAG may be indirectly associated with increased mortality risk through mediators.Results: A total of 2,309 deaths were documented over 8,161 person-years of follow up, including 659 cardiovascular and 399 cancer deaths. In multivariate analyses, higher ACAG levels had a significant correlation with an increase in all-cause (HR, 1.58; 95% CI, 1.38-1.81; P=0.001), cardiovascular (HR, 1.34; 95% CI, 1.05-1.72; P=0.019), and cancer (HR, 1.41; 95% CI, 1.02-1.96; P=0.018) mortality rates than the controls. Results of the mediation analysis showed that altered levels of C-reactive protein and estimated glomerular filtration rate (eGFR) explained 7.867% and 7.669% of the relation between serum ACAG and all-cause mortality, respectively (all P<0.05). Total cholesterol and HbA1c mediated 15.402% and 14.303% of the associations with cardiovascular mortality, respectively (all P<0.05).Conclusions: Higher ACAG levels were significantly associated with increased all-cause, cardiovascular, and cancer mortality. Researchers suggest that patients with T2D who control ACAG in a normal state may be at a lower risk of mortality.